New short interleaver design for Turbo codes - LIU Wen-ming; ZHU Guang-xi; HE Ye-jun (Tongxin xuebao)
The effect of the self interleaving distance and correlative interleaving distance of the interleaver on the decoding performance was investigated. The functions of interleaving distance were put forward and a design rule of interleaver was presented. Based on the analysis, a new interleaver generated by using a linear recursion was proposed. Simulation results show that they exhibit good bit error performance.